High Fat Diet-Induced Hepatic 18-Carbon Fatty Acids Accumulation Up-Regulates CYP2A5/CYP2A6 via NF-E2-Related Factor 2 - Wang, Xing-he; Cui, Xiao-xu; Sun, Xiao-qi; Wang, Xing-hui; Li, Xiao-chong; Qi, Yue; Li, Wei; Han, Mei-yu; Muhammad, Ishfaq; Zhang, Xiu-ying (Frontiers in Pharmacology, 2017)
Abstract To investigate the role of hepatic 18-carbon fatty acids (FA) accumulation in regulating CYP2A5/2A6 and the significance of Nrf2 in the process during hepatocytes steatosis, Nrf2-null and wild type mice fed with high-fat diet (HFD), and Nrf2 silenced or over expressed HepG2 cells administered with 18-carbon FA were used. HE and Oil Red O staining were used for mice hepatic pathological examination. The mRNA and protein expressions were measured with real-time PCR and Western blot. The results showed that hepatic CYP2A5 and Nrf2 expression levels were increased in HFD fed mice accompanied with hepatic 18-carbon FA accumulation. The Nrf2 expression was increased dose-dependently in cells administered with increasing concentrations of stearic acid, oleic acid, and alpha-linolenic acid. The Nrf2 expression was dose-dependently decreased in cells treated with increasing concentrations of linoleic acid, but the Nrf2 expression level was still found higher than the control cells. The CYP2A6 expression was increased dose-dependently in increasing 18-carbon FA treated cells. The HFD-induced up-regulation of hepatic CYP2A5 in vivo and the 18-carbon FA treatment induced up-regulation of CYP2A6 in HepG2 cells were respectively inhibited by Nrf2 deficiency and Nrf2 silencing. While the basal expression of mouse hepatic CYP2A5 was not impeded by Nrf2 deletion. Nrf2 over expression improved the up-regulation of CYP2A6 induced by 18-carbon FA. As the classical target gene of Nrf2, GSTA1 mRNA relative expression was increased in Nrf2 over expressed cells and was decreased in Nrf2 silenced cells. In presence or absence of 18-carbon FA treatment, the change of CYP2A6 expression level was similar to GSTA1 in Nrf2 silenced or over expressed HepG2 cells. It was concluded that HFD-induced hepatic 18-carbon FA accumulation contributes to the up-regulation of CYP2A5/2A6 via activating Nrf2. However, the CYP2A5/2A6 expression does not only depend on Nrf2.